Biocontrol Efficacy of Bacillus thuringiensis Strain 00-50-5 Against the Root-Knot Nematode Meloidogyne enterolobii in Pepper - Yanfang Sun; Yuan Guo; Yueling Pei; Yuan Chen; Tuizi Feng; Haibo Long (Agriculture)
The root-knot nematode Meloidogyne enterolobii is a major constraint to pepper production in tropical regions. In the long-term practice of root-knot nematode management, bacterial nematicides have attracted increasing attention as effective biocontrol agents. In this study, we evaluated the efficacy of Bacillus thuringiensis strain 00-50-5 (Bt 00-50-5) against M. enterolobii through in vitro, greenhouse and field trials. The cell-free supernatant of Bt 00-50-5 exhibited potent nematicidal activity against second-stage juveniles (J2s) of M. enterolobii, with mortality rates of 98.0% and 100% after 24 h and 36 h of exposure, respectively. In addition, Bt 00-50-5 showed inhibitory effects on the hatching of M. enterolobii eggs, resulting in a remarkable 96.6% reduction in the egg hatching rate after 6 days compared to the control. The pot trials showed that both pepper root galls and egg masses were reduced, and plant growth was improved after treatment with Bt 00-50-5. The field trials showed that the gall index was significantly reduced, with a 66.3% and 68.2% reduction in disease index in 2020–2021 and 2021–2022, respectively, and pepper yield was improved, with a 96.2% and 93.1% increase in yield in 2020–2021 and 2021–2022, respectively, compared to the control. These results indicate the potential use of Bt 00-50-5 as an effective biocontrol agent against M. enterolobii.